Application of Wireless Sensor Network and GPRS Technology in development of Remote Monitoring System - Mengxing Chang; Qiuhong Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
The paper presents application of wireless sensor network and GPRS technolog in development of remote monitoring system. The remote monitoring system harnesses embedded technology, wireless sensor network and the GPRS mobile communication technology, to solve the problem of data transmission between data acquisition system and control equipment. This system is real-time, high reliability. This paper chooses ZigBee as protocol based on wireless sensor network. Wireless monitoring system using GPRS technology enables real-time, reliability has been greatly improved. Finally the successful application of intelligent home furnishing system proves the feasibility of this scheme. DOI: http://dx.doi.org/10.11591/telkomnika.v13i1.6894